2010
DOI: 10.1124/jpet.109.164608
|View full text |Cite
|
Sign up to set email alerts
|

A Naphthoquinone Derivative Can Induce Anemia through Phosphatidylserine Exposure-Mediated Erythrophagocytosis

Abstract: A naphthoquinone derivative, ␤-lapachone (␤L; 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione), is receiving huge attention for its potent therapeutic effects against various diseases. However, during the preclinical safety evaluation, repeated oral treatment of ␤L in rats induced anemia, i.e., a significantly decreased erythrocyte count. In this study, in an effort to elucidate the mechanism underlying the ␤L-induced anemia, we investigated the effects of ␤L on erythrocytes with freshly isolated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…β-Lapachone (Lap), a well studied NQO1 substrate, has been identified as a promising agent for various cancer therapy [18]. However, repeated oral treatment of Lap induces anemia in both rats and humans which may greatly limit its application [19], [20]. Another limitation of Lap is its NQO1 specific activity can only be realized within a relatively narrow concentration range and exposure time window [18]; it is questionable whether such a condition can be well controlled in the in vivo states.…”
Section: Introductionmentioning
confidence: 99%
“…β-Lapachone (Lap), a well studied NQO1 substrate, has been identified as a promising agent for various cancer therapy [18]. However, repeated oral treatment of Lap induces anemia in both rats and humans which may greatly limit its application [19], [20]. Another limitation of Lap is its NQO1 specific activity can only be realized within a relatively narrow concentration range and exposure time window [18]; it is questionable whether such a condition can be well controlled in the in vivo states.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that oral treatment of rats with β-lapachone induced anemia that was attributed to increased phosphatidylserine externalization and erythrophagocytosis induced by ROS [56]. However, the extents of reduction in erythrocyte cell numbers in adult rats (22%~26%) and zebrafish embryos (75%~90%) upon β-lapachone treatment greatly differed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, any of the small molecules listed in Table 2 could, at least in theory, accelerate the eryptosis of plasmodium-infected erythrocytes and thus counteract the rise of parasitemia. It is noteworthy, that the malaria pathogen plasmodium is not expected to become resistant to therapeutic acceleration of eryptosis, which is accomplished by cell mechanisms and is Estramustine 75 --100 µM + + [67] Ferutinin 30 µM + [68] Fluoxetine 25 --50 µM + [69] FTY720 10 µM + [1,2] Fumagillin 10 --100 µM + + [70] Gambogic acid 100 --500 nM + + [1,2] Gedunin 12 µM + [71] Geldanamycin 5 --50 µM + + [72] Glycation 40 mM glucose + Honokiol 5 --15 µM + + [74] Indoxyl sulfate 50 --600 µM + + Lumefantrine 3 --24 µg/ml [76] Lysophosphatidic acid 2.5 µM + + [77] Mercury 1 µM + + [78] Methyldopa 6 µg/ml + + Mitoxantrone 10 µg/ml + + [55] Monensin 0.1 µg/ml + [1,2] Mushroom tyrosinase 7 U/mL + + [81] Naphthoquinone derivatives 10 µM + [82] Nitazoxanide 1 --50 µg/ml + [83] Novobiocin 500 µM + + [84] Nystatin 5 --15 µg/ml + [85] Ochratoxin A 2.5 --10 µM + + Patulin 2.5 --10 µM + [87] Penta-O-galloyl-b-D-glucose 10 --50 µM + + [88] Peptidoglycan 10 µg/ml + [89] Phloretin 100 µM + [90] Phorbol-12 myristate-13 acetate…”
Section: Expert Opinionmentioning
confidence: 99%